Changes in the Hip of Youth Hockey Players over 3 Seasons as Seen on MRI and Physical Exam. Issue 7 (29th July 2014) - Philippon, Marc J.; Ho, Charles; Briggs, Karen K.; Ommen, N. Dawn
Objectives: It has been reported that relative to other sports participants, ice hockey players suffer from cam femoroacetabular impingement (FAI) in higher numbers. Alpha angles have been reported to increase with the likelihood of symptomatic FAI. It is unclear how alpha angle and other factors related to FAI change over early childhood years. The objective of this study was to track youth hockey players over 3 years and determine if factors associated with FAI increased as they aged and increased skating time. Methods: 15 asymptomatic youth ice hockey players(ages 10 to 16 years) had pre-participation screening prior to starting youth hockey season. All players started in the peewee(ages 10 to 12) division and moved up in divisions over the 3 years. All players had a clinical hip examination consisting of the FABER test, impingement testing, and measurement of hip internal rotation. An limited screening MRI was taken and the hip alpha angle was measured and labral tears were documented. Results: These youth hockey players played an average of 42 weeks/year over 3 years. Four goalies were included. Players had significantly increased alpha angle by year 3 of screening. The average alpha angle at year 1 was 56(range 45 to 63), year 2 average was 59 (range 52 to 68) and year 3 average was 75 (range 64 to 88). By year 3, 12/15 had asymptomatic labral tears. The 3 players who did not have labral tears had alpha angles of 60, 62, and 64 degrees. There were no significant changes in internal rotation over the 3 years. There was a trend toward decreased internal rotation in goalies. One goalie reported symptoms after the completion of the 3 rd season when he was 16 years old. Conclusion: Young ice hockey players show increasing alpha angles and development of asymptomatic labral tears. Stresses inherent to ice hockey likely enhance the development of a bony overgrowth on the femoral neck contributing to cam FAI. Further study into the etiology of the increase in the alpha angle in ice hockey players is recommended to determine if preventative measures may be adapted to decrease the incidence of hip symptoms which decrease activity level.